Hormonal contraception with desogestrel-induced medication use - S A Levakov; N A Sheshukova (Гинекология, 2014)
This article presents current information on existing methods hormonal contraception, covered medical and clinical aspects acceptability of hormonal contraceptives.An important emphasis is made on the benefits of Laktinet® in women of postpartum period, and breastfeeding women older than 40 years.